POLITICAL LOYALTY AND CITIZENSHIP: A SOCIOLOGICAL ANALYSIS OF IRAQ'S DEMOCRATIC LANDSCAPE - Hussein, Kamal Razaq (PT. Antis International Publisher, 2025)
Objective: The study analyzes how political allegiance impacts citizenship rights while investigating how sectarianism affects political allegiance and explores how civil society organizations and youth movements boost political engagement toward changing political allegiance in Iraq. Method: The examination employed quantitative methods by acquiring data using an online structured questionnaire from 200 participants, including questions about political loyalty, sectarianism, citizenship rights, and involvement in civil society groups and youth movements, with regression and Pearson correlation methods applied to analyze relationships between significant variables. Result: The results indicate that political loyalty has a strong effect on citizenship rights, accounting for 62.3% of the variance, sectarianism has a strong effect on political loyalty with a positive correlation of R = 0.788, and civil society organizations and youth movements were also found to increase political participation and transform political loyalty, with youth activism having the strongest positive correlation (r = 0.702) with political participation. Novelty: This research closes a significant knowledge gap by presenting a sociological investigation of how political loyalty, sectarianism, civil society actors, and youth movements interact in influencing citizenship practice, pinpointing the empowerment possibilities of civil society initiatives for developing democratic engagement and countering sectarianism.